Adam Smith and Amartya Sen: Markets and famines in pre-industrial Europe - Cormac Ó Gráda (University College Dublin, Department of Economics, 2002)
How markets perform during famines has long been a contentious issue. Recent research tends to associate famine with market segmentation and hoarding. The evidence of this paper, based on an analysis of the spatial and temporal patterns of price movements during four famines in preindustrial Europe, is that markets functioned `normally' in times of crisis.
hdl:10197/497
Keywords: 330; Hungersnot; Wirtschaftsgeschichte; Europa; Markteffizienz